OP15 Associations with crystal methamphetamine use in a large cross-sectional, community-based sample of UK men who have sex with men. (13th September 2016) - Melendez-Torres, GJ; Bonell, C; Hickson, F; Bourne, A; Reid, D; Weatherburn, P
Abstract : Background: Crystal methamphetamine ('meth') use by men who have sex with men (MSM) is an ongoing public health issue in the UK. Concern has increased with the emergence of 'chemsex' in the last five years (combining of drugs with sex). Understanding the characteristics of MSM using meth is important to develop targeted harm reduction and HIV prevention interventions. However, the last study to examine the demographic and socio-sexual risk factors for meth use in national samples used data from 2007. Methods: We used data from the 2014 Gay Men's Sex Survey, an online community-based survey of MSM in the UK conducted in summer 2014. MSM aged 16 and above and resident in the UK were recruited via a variety of online dating sites and community email bulletins. We used logistic regression to relate socio-sexual and demographic risk factors to last-year use of meth. Each variable was entered into a univariate model before a multivariate model was estimated with all risk factors. Results: Of the 16, 565 MSM contributing to the analysis sample, 4.5% (n = 747) reported last-year meth use. In univariate models, compared with those aged 20–29 years, men aged 30–39 years of age (OR 2.24, 95% CI [1.84, 2.72]) or 40–49 years of age (2.21, [1.80, 2.72]) were more likely to use meth. Compared to MSM who lived in London, MSM in the Midlands and East of England (0.17, [0.13, 0.21]) and in the North of England (0.17, [0.13, 0.22]) were less likely to have used meth. MSM whose last HIV test was positive were more likely (7.37, [6.28, 8.65]) than MSM whose last test was negative to have used meth. Odds of meth use increased with the number of non-steady sexual partners with whom unprotected anal intercourse occurred; MSM with two or more such partners were more likely to have used meth (13.83, [10.30, 18.58]) compared to those with no non-steady partners in the last year. Discussion: The use of meth may have risen faster in London than elsewhere, contrasting findings from previous surveys. Future research should continue to investigate patterns of use, including distinguishing between occasional or episodic use and drug use that may be problematic. This cross-sectional, community-based sample may reflect higher risk than the general population of MSM, though it is difficult to establish a sampling frame for this population and longitudinal studies may better highlight temporal relationships between drug use, sexual risk and possible harms.